A REVIEW ON STERCULIA FOETIDA L. AND IT’S POTENTIAL FOR DEVELOPMENT IN THE DRY AREAS OF VIETNAM - Phạm Trọng Nhân; Lê Hồng Én; Huỳnh Thị Kiều Trinh (Tạp chí Khoa học Đại học Đà Lạt, 2019)
Sterculia foetida L. is well adapted to many soils and is valuable in the food, cosmetic, medicine, pesticides, bio-oil, beverage, and furniture industries. More knowledge is needed about its value and uses, including resin tapping and storage, propagative methods and cultural uses. The literature on Sterculia foetida L. was summarized to provide guidance and to bring together key recommendations needed to successfully rehabilitate degraded lands and forests. Based on this review, we build on recent work to provide critical advice and state explicit objectives related to planting and developing of this species in Vietnam.